Efforts to Increase Students' Interest in Learning Using Image Media Water Cycle Materials in Science Class 5 SDN 3 Dermaji, Lumbir District Banyumas District - Alfi Mukhlis Kurniawan; Amalia Nurul Azizah (Universitas Sebelas Maret, 2021)
This study aims to increase the learning interest of grade 5 students at SDN 3 Dermaji by using media images on the water cycle material. This research was conducted at SDN 3 Dermaji, Lumbir District, Banyumas Regency. The research design used was Classroom Action Research (CAR), which consisted of two cycles with each cycle consisting of two actions. The research subjects were 25 grade 5 students at SDN 3 Dermaji. Data obtained through observation, interviews, and interest in learning tests. Data were analyzed using qualitative and quantitative analysis. The results of the study show that the use of media images in the water cycle material can increase students' learning interest. In cycle I, the average score of interest in learning was 67.6 with a percentage of learning completeness of 56%, while in cycle II, the average score of interest in learning increased to 84.2 with a percentage of learning completeness of 88%. This shows that the use of media images is effective in increasing students' learning interest. In addition, the results of the study also show that students find it easier to understand the material and are more interested in learning to use media images. Based on the research results, it is suggested that the use of media images in learning materials can be increased, and the use of other learning media also needs to be implemented to meet students' learning needs. In addition, it is also necessary to have attention and support from all related parties so that the use of media images in learning can run well and effectively.